One-bottle drainage system in Tuberculosis-Associated Secondary Spontaneous Pneumothorax: A Case Report : - Gede Ardi Saputra; Pratama, Muhammad Reqza; Munthe, Eva Lydia; Swastini, Ni Putu (Medula, 2024)
Tuberculosis (TB) is one of the ten leading causes of death in the world. Indonesia ranks second in the world in terms of TB cases and is the largest contributor to the increase in new cases. This study reports a man suffering from TB with a rare complication, secondary spontaneous pneumothorax. We describe a 27-year-old male smoker who reported sudden shortness of breath two hours ago, accompanied by pain in the left side of the chest when breathing. He is currently undergoing advanced antituberculosis treatment. A physical examination and chest X-ray revealed spontaneous pneumothorax. A GeneXpert sputum test 2 months ago was positive for Mycobacterium tuberculosis. We performed chest tube placement. After 19 days, the patient showed clinical improvement and responded well to treatment. In conclusion, secondary spontaneous pneumothorax (SSP) in tuberculosis patients is a rare occurrence. The patient received chest tube placement, as well as oxygen therapy, anti-TB drugs, and chest physiotherapy. We treated the individual using a one-bottle system because this type of pneumothorax is simple, practical, and easy for mobile individuals.